2018
DOI: 10.1002/cpe.4476
|View full text |Cite
|
Sign up to set email alerts
|

A predictive Decision Support System (DSS) for a microalgae production plant based on Internet of Things paradigm

Abstract: Summary The production of microalgae represents a large and rapidly expanding market with several applications in the fields of food, pharmaceutics, cosmetics, and energy. Microalgae are photosynthetic aquatic microorganisms whose growth is mainly controlled by a few environmental parameters: temperature, light, pH, and nutrient availability. For this reason, monitoring and controlling such parameters is crucial for their production. At the same time, the development of mathematical models to simulate the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Although in recent years there has been a plethora of studies on technology readiness and technology acceptance from the consumer's perspective, industrial context, or in the organizational adoption as a whole [5,10,14,[27][28][29][30][31][32][33][34][35][36][37], there is scarcity of research from an employee's perspective as the unit of analysis for readiness and technology acceptance [11,36,[38][39][40][41][42] in e-business environments. Moreover, no studies of such nature are found for technology intensive environments.…”
Section: Employees Customersmentioning
confidence: 99%
“…Although in recent years there has been a plethora of studies on technology readiness and technology acceptance from the consumer's perspective, industrial context, or in the organizational adoption as a whole [5,10,14,[27][28][29][30][31][32][33][34][35][36][37], there is scarcity of research from an employee's perspective as the unit of analysis for readiness and technology acceptance [11,36,[38][39][40][41][42] in e-business environments. Moreover, no studies of such nature are found for technology intensive environments.…”
Section: Employees Customersmentioning
confidence: 99%
“…The results of training various networks with different structures are presented in this section. By training the networks with different number of neurons (3)(4)(5)(6)(7)(8)(9)(10)(11) in the hidden layer using ICA with parameters presented in Table 7, the ANN models were developed. For each response totally 18,000 networks were trained and evaluated.…”
Section: Integrating Artificial Neural Network and Imperialist Competmentioning
confidence: 99%
“…Using computers and the Internet has shown a great potential to solve these types of problems by reducing the aforementioned undesirable effects. There are myriad of computer-based techniques and recently IoT that are used widely to solve engineering problems [9]. ANNs are one of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…11 The major impediments toward the success of scientific workflows may be due to, first, the specific domain knowledge, and second, the distributed data over the internet, although the internet of data paradigm has stimulated numerous data analysis and mining applications. [12][13][14] In our research, we focus on host-pathogen protein-protein interactions, which we anticipate in delivering a workflow to bridge the aforementioned research gaps. This work is a substantial extension of the conference version, 3 which has initially investigated the performance of the two-layer model by one feature representation algorithm.…”
Section: Introductionmentioning
confidence: 99%